Plasma metabolic alterations in patients with severe obesity and non‐alcoholic steatohepatitis. Issue 3 (11th December 2019) - Cabré, Noemí; Luciano‐Mateo, Fedra; Baiges‐Gayà, Gerard; Fernández‐Arroyo, Salvador; Rodríguez‐Tomàs, Elisabet; Hernández‐Aguilera, Anna; París, Marta; Sabench, Fàtima; Del Castillo, Daniel; López‐Miranda, José; Menéndez, Javier A.; Camps, Jordi; et al.
Summary: Background: Obesity can influence hepatic mitochondrial function, and cause non‐alcoholic steatohepatitis (NASH). Diagnosis and follow‐up rely on invasive liver biopsy so blood‐based markers are urgently required. Aim: To investigate whether values of circulating metabolites from energy and one‐carbon (1‐C) metabolism may: (a) reflect hepatic mitochondrial flexibility failure and (b) act as NASH biomarkers. Methods: Patients with severe obesity undergoing bariatric surgery (n = 270) were investigated using quantitative targeted plasma metabolomics. Comparisons were with non‐obese controls without liver disease (n = 50). Obese patients with NASH (n = 53) and without NASH (n = 130) representing extreme groups of liver disease were assessed to test the diagnostic ability of the measured circulating metabolites. Paired liver biopsy and plasma samples from NASH patients were available 1 year post‐surgery and were evaluated to monitor metabolomic changes with liver damage resolution. Results: We identified correlations between human liver metabolism and obesity. High‐plasma α‐ketoglutarate (α‐KG) and lactate concentrations in NASH patients indicating citric acid cycle replenishment via glutaminolysis might also be a crucial point in NASH onset. Plasma measurements of α‐KG, β‐hydroxybutyrate, pyruvate and oxaloacetate reduced the uncertainty in clinical diagnosis of NASH [area under receiver operating characteristic curve (AUC) of 0.826] and predicted NASH resolution without ambiguity (AUC of 0.999). Conclusion: Changes in plasma mitochondrial metabolites appear to be associated with NASH. These metabolic responses may be dynamically remodelled following resolution of liver damage through massive weight loss.